Clarification of the Consideration of the Survival of the Tanzih with the Manifestation in Pictures (Ibrahim bin Hassan bin Shihab Al-Din Al-Shahrani Al-Shahrazouri Al-Korani) died: 1101 AH - Study and Verification- - Taha , Ali (Islamic Sciences Journal, 2023)
ABSTRACT Praise be to Allah, Lord of the Worlds, and prayers and peace be upon our master Muhammad, his family and companions, and those who followed his path until the Day of Judgment and beyond. This is an Verification of the message: “Examination of the Survival of the Contemplation with the Transfiguration with Pictures,” by its author: (Ibrahim bin Hassan bin Shihab Al-Din Al-Shahrani Al-Shahrazuri Al-Kurani - deceased: 1101 AH -). Referring the sayings to their owners, defining the ambiguous, controlling and correcting the words, and proving the differences between the two versions, in order for the message to appear in the clearest and most useful way. The author, may Allah Almighty have mercy on him,has explained the issue of seeing Allah Almighty on the Day of Resurrection and that people differ in their vision, and that each one of them sees Allah in the manner of his belief that he had in this world. We ask Allah Almighty to grant us his vision on the Day of Resurrection.